2009
DOI: 10.1097/opx.0b013e3181be0712
|View full text |Cite
|
Sign up to set email alerts
|

Optic Nerve Heads in Pediatric African Americans Using Retinal Tomography

Abstract: ONH parameters were not related to age and refractive error, and only C/D area ratio and linear C/D ratio were greater in boys than girls in a clinical sample of African American children. These measures of normative ONH parameters and range of interocular differences may be helpful in clinical pediatric eye care to facilitate identification of African American children with abnormal optic discs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 33 publications
4
4
1
2
Order By: Relevance
“…Other HRT findings in our study from the emmetropic group resembled the results of Larsson et al [11]. Pang et al investigated ONH in pediatric African Americans with refractive errors up to + 6.5 D [12]. In that study, the average disc, cup and rim areas in hyperopic and emmetropic children were much larger than in our study.…”
Section: Hrtsupporting
confidence: 88%
See 2 more Smart Citations
“…Other HRT findings in our study from the emmetropic group resembled the results of Larsson et al [11]. Pang et al investigated ONH in pediatric African Americans with refractive errors up to + 6.5 D [12]. In that study, the average disc, cup and rim areas in hyperopic and emmetropic children were much larger than in our study.…”
Section: Hrtsupporting
confidence: 88%
“…However, there was no correlation between age and other HRT parameters. This is consistent with an HRT study of African American children, in which no effect of age on HRT parameters was detected [12]. Larsson et al identified a weak correlation between age and cup/ disc ratio and mean cup depth; however, no correlation was reported for any other HRT parameters [11].…”
Section: Influence Of Age On Onh Parameterssupporting
confidence: 88%
See 1 more Smart Citation
“…Apesar disso, em termos individuais, o aumento pode ser significante (16) . Por outro lado, outros autores, relatam que os parâ-metros da cabeça do nervo óptico não estão relacionados com idade (17)(18) . Apesar dessa controvérsia, considera-se a importância de conhecer os valores da relação E/D em adolescentes, pois esse parâmetro, registrado em retinografias, permitirá comparações na eventualidade de os mesmos apresentarem, futuramente condições indicativas de glaucoma.…”
Section: Discussionunclassified
“…Diferenças de razão escavação/disco de 0,2 podem aparecer em 1 a 6% da população adulta normal e assimetrias de 0,3 em 1% da população geral (12)(13)(14)(15) . Apesar da diversidade de estudos realizados em adultos e dos relatos de alguns estudos que incluíram crianças e adolescentes (16)(17)(18) a literatura, ainda, carece de dados referentes à medida escavação/disco em jovens na faixa etária de 14 a 18 anos de idade, época da vida em que ocorrem grandes mudanças no organismo, inclusive no globo ocular.…”
Section: Resumo Introduçãounclassified